Same, same but different: Attention bias for food cues in adults and adolescents with anorexia nervosa. Issue 6 (26th March 2019) - Werthmann, Jessica; Simic, Mima; Konstantellou, Anna; Mansfield, Phoebe; Mercado, Daniela; van Ens, Welmoed; Schmidt, Ulrike
Abstract: Objective: Attention processing for food may be biased in people with Anorexia Nervosa (AN). However, previous studies have had inconsistent results. This is likely to be due to indirect assessment of attention, which does not inform on the underlying attention processes, and/or the heterogeneity of participants across studies, testing either adults or adolescents with AN, that is, people at very different developmental and illness stages. Method: Eye‐tracking was employed as a direct assessment of attention during a visual probe task with food versus non‐food pictures. Attention bias for food was measured in 39 adults and 34 adolescents with AN and in 53 adults and 31 adolescents without AN. Results: All participants had a direction bias for food, specifically for high‐calorie food. However, adults with AN subsequently avoided maintaining attention on food versus non‐food cues, compared to adults without AN. Adolescents with or without AN demonstrated increased attention maintenance on food versus non‐food cues, and, contrary to our hypothesis, did not differ in their attention bias for food cues. Accordingly, adults with AN differed significantly from adolescents with AN in attention maintenance for food cues: while adolescents with AN showed significantly increased attention maintenance on food stimuli, adults avoided maintaining attention on food cues. Discussion: Adults with AN may apply attention strategies to facilitate restrictive eating. This strategy is absent in adolescents with AN. This difference in food‐related attention bias between adolescents and adults with AN suggests that attention biases develop over time as the illness progresses.